ANALISIS MODEL PENERIMAAN DAN PENGGUNAAN SISTEM INFORMASI WEBSITE PADAMU NEGERI OLEH PENGGUNA MENGGUNAKAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Ismarmiaty Ismarmiaty (Universitas Bumigora, 2016)
This study analyzes user acceptance and usage model for Padamu Negeri web-based e-government Kemdikbud information system application with UTAUT model modification refers to Venkatesh (2003) and Ash-Shobi (2011). Respondent were 107 person of user of the application. T and F test results lead to the conclusion that the variables Performance Expectance (PE), Effort Expectance (EE), Social Influence (SI), Trust of Internet (TI) and Trust of Intermediary (TOI) simultaneously influence on Behavioural Intention (BI) but only variables SI and TI are significant partial influence on BI. Another result was variables Facilitating Condition (FC) and Behaviural Intention (BI) simultaneously influence on Behavioural Usage (UB) but only FC variables significantly influence the UB. Test validity and reliability as well as the assumptions of classical test data shows worth as a measure of this analysis.